America's shifting emphasis to the Pacific - Jens D. Biermeier (Intereconomics, 1985)
East Asian nations, which not long ago were counted among the more backward, are emerging as dramatically expanding markets as well as tough competitors for the United States. Predictions are that the Pacific-rim economy will expand twice as fast as the rest of the world. Professor Jens Biermeier shows that there has been a shift in the trading pattern of the United States away from Europe towards Asia as well as a shift of US political and strategic interests from the Atlantic to the Pacific in recent years.
Keywords: 330